Guessing Game Effectiveness for Improving Student Speaking Skill in Elementary School - Suwarsih Madya; Fitria Ayu Meningsih (Celt: A Journal of Culture, English Language Teaching & Literature, 2021)
English speaking skills are very important because Game is Communicative Language Teaching (CLT) which will create an atmosphere that will increase students' desire to learn languages. However, there is an assumption that learning with games makes students undisciplined and difficult to do because it requires a long time and many teachers. This study aims to determine the effect of learning English using a guessing game method on the speaking skills of elementary school students. This research is a one-group pre-test post-test design that was implemented at the Islamic Elementary School in Yogyakarta. The research sample consisted of 68 elementary school students in grade 6 in 2019. The sampling technique used was total sampling. The research was conducted by classroom action with intervention in the form of learning English with guessing games for 3 months in two cycles. The measured learning outcomes are speaking skills in the form of pronunciation, vocabulary, grammar, fluency, and understanding. the assessment was carried out before and after the intervention. The data were processed using the Wilcoxon test. The results showed that the students' speaking skills improved after going through the learning process with guessing games. The speaking skills that have improved significantly are pronunciation, vocabulary and fluency. Grammar and comprehension improved but not significantly. The conclusion is that the guessing game can improve the students' speaking skills even though it has not covered all its aspects